Wear Analysis of Gear Pump Supply Fat Coating Liquid Cat Food - Wilarso; Mupah Rizal; Asep Saepudin; Asep Dharmanto; Mohd. Yuhazri Yaakob; C.W. Mohd Noor (Universitas Medan Area, 2024)
Trochoid Top 208 HBM Nippon Oil Pump (NOP) is an important unit in the cat food manufacturing process. The pump system acts as a fluid transfer agent by directing fluid from the tank to the nozzle channel. Based on Pareto and Fishbone diagram data, it was found that the main causes of problems that often occur with the Nippon Oil Pump (NOP) Type Trochoid Top 208 HBM are filter blockage (5 times) and pump gear wear (3 times). The aim of this analysis is to reduce damage to the Nippon Oil Pump (NOP) Type Slocoid Top 208 HBM and increase the production of higher quality cat food. From the results of the analysis carried out, there were several findings that caused wear on the gear pump, including the viscosity of the material being channeled which was very thick, reaching 1.37 cp. Meanwhile, the pump specifications used are only 2L/minute with a pump motor power of 0.75kw 1.86A 380V. The filter pore particles are too small, reaching 250 microns and the dimensions of the pipe used have a flow pipe diameter of ½”. From the analysis carried out, replace the pump capacity to a minimum of 4L/minute, then replace the filter with pore particles of 600 microns. And the pipe uses a diameter of 1